Using the visual and performing arts to complement young adolescents' "close reading" of texts. Issue 1 (1st January 2017) - McDermott, Peter; Falk-Ross, Francine; Medow, Sharon
Abstract: The educational needs of young adolescents require that curricula include a more expanded set of multiple integrative approaches, including new literacies, and that it be "challenging, exploratory, integrative, and relevant" (National Middle School Association, 2010). Although educators are now focusing on the addition of digital formats to expand presentation of content material in classroom activities, the role of visual and performing arts in these same academic experiences may not be receiving as much attention. Researchers have shown the importance of these aesthetic approaches, and national standards have provided mandates for meeting middle grade students' educational requirements (National Governors Association Center for Best Practices & Council of Chief State School Officers, 2010). In an effort to provide middle grade educators with ideas and students with formats that balance their instruction and motive/engage all students regardless of levels of achievement, a review of research is provided to support these approaches, and two examples of effective classroom activities are explained.